THE ANALYSIS OF THE CONVERGENCE OF HORTICULTURAL SECTOR IN ROMANIA AND COMPARISONS WITH OTHER EU COUNTRIES - Cornelia ALBOIU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper aims to analyze the degree of convergence of the horticultural sector in Romania with other EU member states taking into consideration the competitiveness indicators. In order to be able to establish a causal link between the factors of competitiveness in determining the degree of convergence of the horticultural sector, certain indicators of competitiveness were considered such as the family income of the holding per annul work unit (AWU) and the net added value per unit of annual work. In addition, other indicators were calculated, such as gross value added/AWU and the total value of production. These indicators were calculated based on FADN data, covering the period 2013-2018 including for several other member states of the European Union in order to make comparisons with Romania. The results show a low level of competitiveness compared to all countries analyzed, which indicates that the horticultural sector in Romania is not yet close to achieving the economic convergence with the main EU horticultural sectors of some countries which represent Romania’s competitors in the field.